Hair transplantation in transgender women: case report - Leila David Bloch; Cindy Tiemi Matsumoto (Surgical & Cosmetic Dermatology, 2024)
Hair transplantation is an option for anyone with Androgenetic Alopecia, including transgender patients who want to align their appearance with their gender identity. Thus, hair transplantation can help transform appearance and boost self-esteem, especially if hair loss is a source of gender dysphoria. We report two cases of hair transplantation in transgender patients with good results, using the Follicular Unit Extraction and Follicular Unit Transplantation techniques. Due to the scarcity of specific articles about hair transplantation in this population, we report these cases for a better understanding of the specific needs of these patients.